Nazi Policy on the Eastern Front, 1941 : total war, genocide, and radicalization - Kay, Alex J.; Rutherford, Jeff; Stahel, David, 1975- (Rochester studies in Central Europe., 2012)
This collection of essays provides readers with the most current interpretations of Germany's military, economic, racial, and diplomatic policies in 1941. With its breadth and its thematic focus on total war, genocide, and radicalization, this volume fills a considerable gap in English-language literature on Germany's war of annihilation against the Soviet Union and the radicalization of World War II during this critical year.